Shwan Sebastian – Brahms’ Novel Language - Petruța-Maria COROIU (Studia Universitatis Babeş-Bolyai. Musica)
The sound needs light: the light of a word to unravel its beauty. A performer always lives among metaphors, and the pianist and teacher Shwan Sebastian is himself a metaphor: through his music and – albeit too rarely – through his thoughts and writings about music. This time, his favourite subject refers to Brahms’ last compositions for piano that he approaches as a poet would, in a subtle, intense and profound way. On the verge of its artistic maturity, its interpretative essences are distilled in a musicological discourse of amazing depth, which proves his mastery of a technical analytical apparatus supplying all the relevant details. Everything for music, for its understanding; the author himself confesses that he climbed the ascending path to the “level of interpretation with awareness, because consciousness is the place where musical experience is manifest; the side acquired through analysis stabilizes talent. Through knowledge, we confirm what was undeclared in the beginning” (our translation). The repertoire (interpreted with so much structural awareness and semantic sensitivity) acquires, through this wonderful book, “a structured foundation from an analytical, interpretative and pedagogical perspective, tracing research directions, identifying and analyzing the ideological and compositional profile that sets up and adjusts the interpretation. This book required vast research of Brahms’ work, with a focus on his piano compositions which, to highlight from all perspectives, unavoidably entailed references to other areas of the composer’s music, for example, the symphonic dimension, codified in his entire creation system” (our translation). The author multiple integrating the final opuses by Brahms in a multiple cultural, personal, social, historical and stylistic context, which defines the algorithms behind the creation of the great Romantic composer from the perspective of all discursive parameters (orchestration, harmony, rhetoric and aesthetic expression, musical structures, melody, rhythm and timber, interpretative, compositional and pedagogical valences).